Pengaruh Content Marketing, Live Streaming, and Online Customer Review terhadap Purchase Intention - Wanda Aulya Dewi; Nur Laili Fikriah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Social media platforms like TikTok are extensively utilized by the community to support their events. In addition to being used for entertainment, many businesses use TikTok as a platform for online marketing. Making the most of its features to optimize marketing, such as online customer reviews, live streaming, and content marketing. The purpose of this study is to ascertain how Brand Jiniso's purchase intention is impacted by content marketing, live streaming, and online customer reviews.This research employs a quantitative explanatory methodology and purposive sampling, with 150 potential consumers of the Jiniso brand in Malang City serving as the sample. Data collection techniques include non-probability sampling and purposive sampling. In order to collect primary data for this study, questionnaires with a Likert scale of 1 to 5 were distributed. This study's analysis tool, SmartPLS version 3.0, performs validity and reliability tests to ascertain the test tool's validity and reliability. It also carries out model evaluation tests and hypothesis testing to ascertain the degree to which the relationship between variables is influenced. According to the analysis's findings, online customer reviews, live streaming, and content marketing all significantly influence consumers' intentions to make purchases